Hubungan Intensitas Interaksi Sosial dengan Kemampuan Artikulasi pada Anak Hearing Impairment di SLB YRTRW Surakarta - Apriliza Damas, Ummi; Mangunsong, Roy Romey Daulas (Politeknik Kesehatan Kemenkes Surakarta, 2023)
Background: Some people have problems in social interaction with different factors. One of those who experience communication disorders in social interactions, namely children with Hearing Impairment. The auditory system provides information about the acoustic effects of articulation. Auditory feedback is very important in coordinating articulation processes, because the purpose of speech is to produce intelligible acoustic signals. The prevalence from the Ministry of Social Affairs in 2019, among persons with disabilities in Indonesia, 7.03% are persons with hearing disabilities. Purpose: This study aims to determine whether there is a relationship and description of the intensity of social interaction with articulation skills in children with Hearing Impairment at SLB YRTRW Surakarta. Methods: This research is a quantitative study using descriptive methods through a correlational design. The sampling technique was carried out by purposive sampling with a population of 108 people and a sample of 25 people. Research Results: Based on the research results obtained from data analysis using the Spearman rank analysis test there is a significance value (ρ) of 0.292, which means a significance value (ρ) > 0.05. Then the null hypothesis (Ho) is accepted and the alternative hypothesis (Ha) is rejected. The correlation coefficient (r) between the intensity of social interaction and articulation skills is (r) = -0.219, which means that it has no relationship with weak strength. Conclusion: There is no relationship between the intensity of social interaction and articulation skills in children with Hearing Impairment at SLB YRTRW Surakarta. Keywords: Social Interaction, Articulation Ability, Hearing Impairment